2016
DOI: 10.1002/lary.25706
|View full text |Cite
|
Sign up to set email alerts
|

A description of the anatomy of the glossopharyngeal nerve as encountered in transoral surgery

Abstract: N/A. Laryngoscope, 126:2010-2015, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 14 publications
0
18
0
2
Order By: Relevance
“…After exiting the jugular foreman, the glossopharyngeal nerve is located between the internal carotid artery and internal jugular vein, descending deep to the styloid process. 3 GN is divided into 3 segments based on its relationship with stylopharyngeus muscle, i.e. upper, middle and lower.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After exiting the jugular foreman, the glossopharyngeal nerve is located between the internal carotid artery and internal jugular vein, descending deep to the styloid process. 3 GN is divided into 3 segments based on its relationship with stylopharyngeus muscle, i.e. upper, middle and lower.…”
Section: Discussionmentioning
confidence: 99%
“…Lower segment starts from to intersection of the GN with the inferior border of the stylopharyngeus muscle to its end at the tongue base. 3 The middle segment of the GN is covered by the stylopharyngeus muscle anteriorly. In this segment, it gives off branches innervating the stylopharyngeus muscle and branches to pharyngeal wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported that the base of the styloid process, the styloid muscles, transverse process of the atlas and the internal and external carotid arteries are clinically available to identify the GPn in the extraoral or intraoral surgical procedures (Bejjani et al ., ; Özveren et al ., ; Prades et al ., ; Wang et al ., , ). Apart from the atlas that was not examined, this study also suggests that these structures are useful to find the GPn.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, the intraoral approach leaves no scars and is a relatively straightforward and less time-consuming procedure; however, it does not permit the complete exposure of the surgical field and is accompanied by the poor exposure to control bleeding with a higher risk of deep cervical infection. Previously, surgical anatomical studies have revealed that some structures, such as the styloid muscles, are clinically available to identify the GPn (Bejjani et al, 1998;Özveren et al, 2003;Prades et al, 2014, Wang et al, 2016. A study reported that the GPn was found deeply to the superior constrictor and at the intersection of the palatopharyngeal arch with the base of the tongue in the intraoral approach (Lim et al, 2013).…”
mentioning
confidence: 99%